2021
DOI: 10.2113/2021/8047321
|View full text |Cite
|
Sign up to set email alerts
|

Research on Structural Evolution and Microseismic Response Characteristics of Overlying Strata during Repeated Mining of Steeply Inclined and Extra Thick Coal Seams

Abstract: Repeated mining is the main factor that leads to development, propagation, and eventual deformation of the overlying strata fissures in the steeply inclined and extra thick coal seams (SIETCS). The evolution of the overlying strata structure is closely related to microseismic events in a mine. As the mining depth increases, the evolution rules of the overlying strata structure become more complicated and can easily induce dynamic disaster accidents. To solve these problems, this paper established a physical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In terms of microseismic research on working face mining in complex heterogeneous space, Xingping Lai et al [16][17] revealed the loss of overlying rock through the characteristics of microseismic "energyfrequency" distribution, cumulative apparent volume, energy index and microseismic b value. Precursor characteristics of stability failure.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of microseismic research on working face mining in complex heterogeneous space, Xingping Lai et al [16][17] revealed the loss of overlying rock through the characteristics of microseismic "energyfrequency" distribution, cumulative apparent volume, energy index and microseismic b value. Precursor characteristics of stability failure.…”
Section: Introductionmentioning
confidence: 99%
“…Steeply inclined thick coal seams are widely distributed in China, with large dip angles and complex geological structures. This makes the mining of steeply inclined thick coal seams a technical problem in mining that has long plagued the development of China's coal industry [1][2][3][4][5][6][7][8][9]. Therefore, in order to meet the safety and high-efficiency production of steeply inclined thick coal seam entering deep mining, it is urgent to carry out mechanical test research on coal samples affected by mining depth in order to better understand the energy accumulation and its evolution law in the process of mining stress increase under the influence of mining depth.…”
Section: Introductionmentioning
confidence: 99%
“…The essence of rockburst is the differential distribution of energy caused by mining disturbance and the inevitable result of the dynamic adjustment in the process of quantitative change [12][13]. The existing energy priming theory shows [14][15][16][17] that the formation of rockburst is often highly correlated with the dynamic-static combination.…”
Section: Introductionmentioning
confidence: 99%